2011
DOI: 10.1074/jbc.m110.154823
|View full text |Cite
|
Sign up to set email alerts
|

Transactivation of the Epidermal Growth Factor Receptor by Heat Shock Protein 90 via Toll-like Receptor 4 Contributes to the Migration of Glioblastoma Cells

Abstract: Extracellular heat shock protein HSP90␣ was reported to participate in tumor cell growth, invasion, and metastasis formation through poorly understood signaling pathways. Herein, we show that extracellular HSP90␣ favors cell migration of glioblastoma U87 cells. More specifically, externally applied HSP90␣ rapidly induced endocytosis of EGFR. This response was accompanied by a transient increase in cytosolic Ca 2؉ appearing after 1-3 min of treatment. In the presence of EGF, U87 cells showed HSP90␣-induced Ca 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
82
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 44 publications
(62 reference statements)
9
82
1
Order By: Relevance
“…Earlier studies from our laboratory and others have shown that EGFR ligands (EGF, HB-EGF) stimulate HK activity in RPTC (9,36,46,54). LPS is also known to induce EGFR transactivation in a variety of cell types, including epithelial cells and renal medullary collecting duct cells (15,24,28,34,61). One hour before LPS administration, mice were treated with the EGFR inhibitor gefitinib (100 mg/kg) or vehicle control and kidneys were harvested 3 h post-LPS.…”
Section: Lps-induced Hk Activity In the Renal Cortex Is Mediated By Ementioning
confidence: 99%
“…Earlier studies from our laboratory and others have shown that EGFR ligands (EGF, HB-EGF) stimulate HK activity in RPTC (9,36,46,54). LPS is also known to induce EGFR transactivation in a variety of cell types, including epithelial cells and renal medullary collecting duct cells (15,24,28,34,61). One hour before LPS administration, mice were treated with the EGFR inhibitor gefitinib (100 mg/kg) or vehicle control and kidneys were harvested 3 h post-LPS.…”
Section: Lps-induced Hk Activity In the Renal Cortex Is Mediated By Ementioning
confidence: 99%
“…Increasing numbers of DAMPs are being reported as candidate agonists of TLRs, and particularly TLR4, including heat shock proteins (HSPs) (HSP70, HSP90), [16][17][18] high-mobility group box 1 (HMGB1) 19,20 and uric acid crystals. 21 These molecules can bind to TLR4, thereby causing inflammatory responses and providing DCs with danger signals, which can be translated into the promotion of an anti-tumor T-cell response.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study EIF2 and PKR were repressed in expression thus implying adaptive anti-apoptotic responses. Moreover, a cross talk between TLR4 and EGFR signalling was reported to promote inflammation and possible cellular transformation 64,65 . In NASH livers, TLR4 was frequently regulated (up-and down-) to evidence activation of the innate immune response.…”
mentioning
confidence: 99%